Association of Increased Arterial Stiffness with Severity of Coronary Artery Disease in Patients With Non-ST- Segment Elevation Myocardial Infarction - Uddin, ABM Nizam; Majumder, Abdullah Al Shafi; Akanda, Md Abdul Kader; Zaman, Shahana; Hossain, Mohammad Anowar; Khan, Ashiqur Rahman; Razzaque, Muhammed Aminur; Das, Pinaki Ranjan; Islam, Md Zahidul; Alam, Kazi Ashraful (Bangladesh Heart Journal, 2019)
Objective: Cardiovascular diseases (CVDs) have become the single largest cause of death worldwide. The scenario is same in Bangladesh. Increased arterial stiffness has been associated with increased risk of CVD. A noninvasive assessment of arterial stiffness may serve as a useful adjunct to the cardiovascular risk stratification and risk management and it would be of value for the examination of larger populations. So, this study was designed to demonstrate the association between CVD and arterial stiffness. Methods: This cross sectional study was conducted in the National Institute of Cardiovascular Disease, Dhaka over a period of ten months starting from January 2014. Patients were purposively selected from those who were admitted in NICVD with acute Non-ST- Segment Elevation Myocardial Infarction (NSTEMI). A total of 80 patients were included in the study. Study patients were divided into two groups on the basis of aortic augmentation pressure (AP), augmentation index (Aix) and augmentation index corrected at heart rate 75/min (AIx@75). Assessment of coronary angiography was performed and severity was assessed by several scoring systems. Results: Significant positive correlation was found between AIx@75 and vessel score (r= 0.70, p=0.001), Friesinger score (r=0.66, p=0.001) and Leaman score (r= 0.69, p=0.001). Logistic regression analysis showed that increased AIx@75 is significantly associated with severe Coronary Artery Disease (CAD) (OR being 5.54). Conclusion: The results indicate that AP, AIx and AIx@75 are predictors of severity of CAD. It may be considered as a recommended test for the evaluation of cardiovascular risk. Bangladesh Heart Journal 2019; 34(2) : 73-79